The use of Arts-Based Research in Chronic Pain: A Scoping Review - Sophie J. Harasymchuk; A. Fuchsia Howard; Heather Noga; Mary T. Kelly; Paul J. Yong (Canadian Journal of Pain)
Background As an emerging approach, arts-based research holds potential to advance understanding of the complex and multidimensional experiences of chronic pain and means of communicating this experiential evidence. This scoping review aimed to map and explore the extent of arts-based research in chronic non-cancer pain, understand the rationale behind using arts-based research methods, and identify directions for future research.Methods Databases PsycINFO, MEDLINE, EMBASE, and CINAHL were searched for eligible English-language articles from inception to November 2022. Out of 1321 article titles and abstracts screened for eligibility, 18 articles underwent full-text screening, with 14 ultimately meeting all inclusion criteria. We conducted a narrative synthesis of data extracted from the 14 reviewed articles.Results The review articles focused on a wide range of chronic non-cancer pain conditions, with 12/14 employing qualitative methods (86%), one repeated measures experimental design, and another a multiphase, multimethod design. Seven articles described the use of drawing, painting, or mixed-media artwork; four used photography; two used body mapping; and one used e-book creation. The rationale for arts-based research included exploring and better understanding patients’ experiences with chronic non-cancer pain, constructing an intervention, and investigating or validating a clinical tool. Nine articles reported that their arts-based research methods produced unintended therapeutic benefits for participants. Recommendations for future research included using arts-based research to better understand and communicate with patients and providers, exploring convergence with art therapy, and designing creative and flexible multiphased studies involving collaboration across disciplines.Conclusions Despite the wide variation in sample and art modalities across reviewed articles, arts-based methods were considered suitable and highly effective for investigating chronic non-cancer pain.